Pengaruh Pembelajaran Bahasa Arab Terhadap Pengembangan Keterampilan Berpikir Kritis Siswa - Afifatun Nafsiyah; Choir, Jihan Alhanin (Journal of Practice Learning and Educational Development, 2024)
This article examines the influence of learning Arabic on the development of critical thinking skills of students. The study uses a qualitative and quantitative approach to identify how aspects of learning Arabic can strengthen students' analytical, evaluative, and creative abilities. Through a survey of 100 students and in-depth interviews with 10 Arabic language teachers, the study explored the role of grammar complexity, text analysis, and interactive teaching methods in improving critical thinking skills. Teachers that teaching methods involving group discussions and debates strengthen students' evaluative and collaborative abilities. In addition, cultural and historical insights gained through Arabic language learning broaden students’ perspectives, making them more critical and analytical in dealing with academic challenges and everyday life. Integrating Arabic learning into school curricula can be an effective strategy to prepare students to face a complex and dynamic world.